Ipsilateral transulnar artery approach catheterizations after failure of the radial approach—Are two sheaths in the same arm safe?. Issue 2 (28th May 2021) - Zafirovska, Biljana; Jovkovski, Aleksandar; Vasilev, Ivan; Taravari, Hajber; Kitanoski, Darko; Petkoska, Danica; Paljoskovska, Savetka; Kostov, Jorgo; Ho, Kalon K.L.; Kedev, Sasko
Abstract: Aims: To assess the safety and feasibility of ipsilateral transulnar access (TUA) after failure of radial access (TRA), with two sheaths placed in the radial and ulnar arteries (RA and UA) in the same arm. Materials and Methods: All consecutive patients with TUA due to inability to cross from ipsilateral TRA in the period from March 2011 until September 2020 were included in the study. We examined clinical and procedure characteristics, access site bleeding and ischemic complications and failure mode of initial TRA. Patients were assessed by duplex ultrasound post‐procedure (at an average of 56 ± 31 months) and followed clinically (functional and pain assessment). Results: In this period, out of 51, 866 patients 112 (0.2%) had a transulnar artery approach due to inability to cross from ipsilateral radial approach. Mean age of patients was 65 ± 11 years with 44% females. Cause for crossover to ipsilateral TUA was inability to cross a RA anomaly in 107 (95%) patients, mostly due to the presence of a "360°" RA loop in 88 patients. Type 3 and 4 EASY Score hematoma was present in 3 patients (2.6%). Six (5.3%) of the patients had new ipsilateral radial artery occlusion noted on duplex on follow up. There were no ulnar artery occlusions detected. There were no clinical or ischemic hand complications seen during a median 4.3 years of follow up. Conclusion: Ipsilateral transulnar artery access following failed radial artery access crossing is safe and successful for coronary angiography and intervention with low rates of complications.